Porphyry Against the Christians - Berchman, Robert (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This volume is a translation of fragments and testimonia of Porphyry's lost work Against the Christians. The first part of the work examines Author, Title, date of composition, and sources. The second part discusses the structure of Against the Christians. The third part focuses on the religious, philosophical, and cultural background of this text. The fourth section constitutes the translation of the fragments and testimonia of Against the Christians. This work is especially important for historians of religion, philosophy, and Biblical Studies for it is an excellent example of a pagan tradition of scriptural interpretation and criticism of Christianity.